Phase Transformation and Deformation Behavior of Steels with Different Content of Metastable Austenite - KLEIN, Matthias Walfred; SKORUPSKI, Robert; SMAGA, Marek; BECK, Tilmann (Engineering Transactions, 2017)
Abstract: In this investigation three steels HCT 780T, AISI 347 and HSD® 600 with different content of metastable austenite and different austenite stability were monotonically loaded at ambient temperature. Using x-ray diffraction and scanning electron microscopy changes in the microstructure were characterized in detail. Hence, the most important mechanisms, which occur by deformation were determined.